Studies of kinetics and thermodynamic parameters of cashmere dyeing with bio-preparation of Urtica Cannabina L, (Proceedings of the Mongolian Academy of Sciences, 2019)
In this study, dyeing Mongolian cashmere with bio-preparation extracted from Urtica cannabina L. was investigated. Dyeing experiments were carried out under varying pH, temperature and contact time. The results have been used to investigate the kinetic and thermodynamic parameters of dyeing cashmere. This process is pH dependent and it has been found that the most suitable condition is pH 4.5. Increase in adsorption capacity with increase in temperature indicates that the dyeing process is endothermic. Thermodynamic parameters like standard affinity (∆µ), standard enthalpy (∆H) and standard entropy (∆S) were evaluated.